Social organization of the eusocial wasp Mischocyttarus cerberus styx (Hymenoptera, Vespidae) - Giannotti, Edilberto [UNESP] (My University, 1999)
The present study was carried out under field conditions in Rio Claro, Southeastern Brazil. The following average life-spans of adults of Mischocyttarus cerberus styx were observed: queens 191.1 days, workers 14.0 days, and males 10.7 days. The short longevity of workers is attributed to the early foraging activity which was performed since the first week of adult age. The life table of the workers revealed high mortality rates during the first three weeks of life. Twenty-four behavioral categories were reported for these wasps and a comparative behavioral catalogue showed that the solitary foundresses (pre-emergence stage) are significantly more active than the queens (post-emergence stage) because they have to perform all the tasks for the nest maintenance. On the other hand, the queens were highly active even in the presence of the workers. The small number of individuals on the nest was the probable cause of the high activity of the queens in the post-emergence colonies. There was no clear division of tasks among workers according to their age (in weeks), so that most of the behavior categories were potentially performed by any worker of any age. Dead queens were replaced by their daughters.